Discourse on Artistic Evidence and the Five Canons of Rhetoric in the 2022 National Education Day Speech - Saputra, Aldi Dwi; Debi, Fanesia; Saddhono, Kundharu (Journal of Pragmatics and Discourse Research, 2023)
Communication is not only aimed at conveying messages, but providing information and persuasion to the other person. The ability to communicate is needed because it has an impact on strengthening the quality of the arguments presented. This study aims to: 1) describe the artistic evidence contained in National Education Day speeches, namely ethos, logos, and panthos., 2) describe the five canons of rhetoric in National Education Day speeches. This research is a qualitative descriptive study. The data collection technique used is the observation and note taking technique. The data used are utterances on National Education Day speeches which contain artistic evidence and the five canons of rhetoric. This study uses data analysis techniques, namely content analysis. The results of this study are that there is artistic evidence and the five canons of rhetoric in National Education Day speeches namely Inventio/Discovery, Dispositio/Arrangement, Style, Pronuntiatio/Delivery, and Memory.